2008
DOI: 10.1007/s10552-008-9145-6
|View full text |Cite
|
Sign up to set email alerts
|

History of benign breast disease and risk of breast cancer among women in China: a case–control study

Abstract: Background: Data from the Shanghai Breast Cancer Study were analyzed to evaluate the relationship between benign breast disease (BBD) and breast cancer among Chinese women with a self-report of physician-diagnosed BBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…Reports culled from western literature implicate premenopausal status, family history of breast cancer, delayed age at first live birth (>25 years) and low parity with increased risk of progression to invasive cancer in women biopsied for benign breast disease. [13][14][15] In 11 we found that majority (88.2%) of women with benign lumps are premenopausal, expressing yet greater concern for invasive cancer risk in young women in these populations. The discovery of seven (2.3%) premenopausal women with proliferative breast disease in this series further increases curiosity for higher cancer risk in young women with specific benign breast lumps.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Reports culled from western literature implicate premenopausal status, family history of breast cancer, delayed age at first live birth (>25 years) and low parity with increased risk of progression to invasive cancer in women biopsied for benign breast disease. [13][14][15] In 11 we found that majority (88.2%) of women with benign lumps are premenopausal, expressing yet greater concern for invasive cancer risk in young women in these populations. The discovery of seven (2.3%) premenopausal women with proliferative breast disease in this series further increases curiosity for higher cancer risk in young women with specific benign breast lumps.…”
Section: Discussionmentioning
confidence: 78%
“…8 The need for proper evaluation of breast lumps is further emphasized by the occurrence of a subset of benign breast lesions categorized as proliferative breast diseases. 8,[13][14][15] These variants confer increased risk of progression to malignancy and their histologic diagnosis mandates mammographic surveillance even after excision. 8,10,[13][14][15] Similarly, the relative risk of invasive breast cancer is higher in women with complex fibroadenomas and remained elevated for decades after diagnosis.…”
Section: South Eastern Nigeriamentioning
confidence: 99%
See 3 more Smart Citations